Equilibrium in Monopolistic Competition - Smithies, A. (Quarterly Journal of Economics, 1940)
The meaning of an imperfect market, 95. — Assumptions underlying the present analysis, 96. — I. The demand functions, 96. — II. Competitor's expectation of his rivais' behavior, 98. — His estimated demand function, 100. — III. Diagrammatic demonstration of attainment of equilibrium, 100. — IV. Equilibrium conditions for the general case, 103. — Conditions affecting the relative magnitudes of p1 and p2 in equilibrium: (1) differences in demand functions, 105; different methods of estimation, 106; (3) cost differences, 106. — V. Conditions under which equilibrium is stable and economically possible, 107. — Cases where the stability conditions are not fulfilled or where equilibrium is economically impossible, 114.